Biocontrol activity and putative mechanism of Bacillus amyloliquefaciens (SF14 and SP10), Alcaligenes faecalis ACBC1, and Pantoea agglomerans ACBP1 against brown rot disease of fruit. (February 2020) - Lahlali, Rachid; Aksissou, Wissam; Lyousfi, Nadia; Ezrari, Said; Blenzar, Abdelali; Tahiri, Abdessalem; Ennahli, Said; Hrustić, Jovana; MacLean, Dustin; Amiri, Said
Abstract: This study aimed at evaluating the antagonistic activity of 16 bacterial strains for the control of brown rot disease caused by Monilinia fructigena, and M. laxa under in vitro and a semi-commercial large-scale trial. These bacterial antagonists' belonging to the genera Alcaligenes, Bacillus, Brevibacterium, Pantoea, Pseudomonas, and Serratia were previously proven effective for control of fire blight of apple. The in vitro dual culture bioassay showed the highest inhibition rates of mycelial growth ranging from 55 to 95% and from 43 to 94% for M. fructigena and M. laxa, respectively. The in vivo bioassay showed moderate and strong inhibition for M. fructigena and M. laxa, respectively. The inhibition rates were dependent on incubation time as well as pathogen virulence. The free-cell bacterial filtrate revealed substantial mycelial growth inhibition ranging from 66 to 86%. The inhibition of conidial germination was from 32 to 78%, suggesting the involvement of metabolites in their biocontrol activity. The antifungal effect of the volatile compounds (VCOs) was observed for all bacteria with mycelial inhibition varying from 12 to 70%. Overall, their efficacy was substantially affected by the nature of the bacterial strains and the modes of action. Taken together, these results underscore that ACBC1 and SF14 for M. fructigena and SP10 and ACBP1 for M. laxa were the most effective bacterial strains. These strains were confirmed effective in a semi-commercial large-scale trial. Interestingly, their efficacies were found to be comparable to those of both commercial BCAs ( B. subtilis Y1336 and P. agglomerans P10c), but slightly lower than thiophanate-methyl fungicide. The ability of most bacterial strains to produce lytic enzymes (Amylase, Protease or Cellulase) and lipopeptides (bacillomycin, fengycin, iturin and surfactin) was demonstrated by biochemical and molecular analyzes. Therefore, our findings suggest that the bacterial antagonists ACBC1, SF14, SP10 and ACBP1, have the potential to prevent brown rot disease. Highlights: Role of 16 bacterial strains in suppressing brown rot disease on fruit ( M. fructigena and M. laxa) was investigated. In vitro mycelial growth and brown rot on apple fruits was significantly reduced by bacterial strains. Bacterial free-cell filtrates and volatile organic compounds reduced significantly the in vitro mycelial growth. Two bacterial strains highly effective were selected for each pathogenic fungus. These bacterial strains were effective in controlling brown rot preventively and posses at least two genes of lipopeptides with possibility to produce some extracellular enzymes.